1988
DOI: 10.1007/bf02371188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity and inoculation on growth, nitrogen fixation and nutrient uptake ofVigna radiata (L.) Wilczek

Abstract: This study reports the effect of salinity and inoculation on growth, ion uptake and nitrogen fixation by Vigna radiata. A soil ECe level of 7.5 dS m ~ was quite detrimental causing about 60% decline in dry matter. and grain yield of mungbean plants whereas a soil ECe level of 10.0 dS m-t was almost toxic. In contrast most of the studied strains of Rhizobium were salt tolerant. Nevertheless, nodulation, nitrogen fixation and total nitrogen concentration in the plant was drastically affected at high salt concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 14 publications
8
31
0
3
Order By: Relevance
“…Numerous researchers (Wilson 1970;Singleton and Bohlool 1984;Grattan and Maas 1988;Hafeez et al 1988;Wignarajah 1990;Delgado et al 1994;Cordovilla et al 1996) have reported that salt treatment reduced plant growth markedly even at low levels. However, we observed that the response of A. pseudoalhagi plants to salt was different in a sense that the whole plant dry weight increased approximately by 170% in the 50 mM treatment at 10 DAT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers (Wilson 1970;Singleton and Bohlool 1984;Grattan and Maas 1988;Hafeez et al 1988;Wignarajah 1990;Delgado et al 1994;Cordovilla et al 1996) have reported that salt treatment reduced plant growth markedly even at low levels. However, we observed that the response of A. pseudoalhagi plants to salt was different in a sense that the whole plant dry weight increased approximately by 170% in the 50 mM treatment at 10 DAT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Il apparaît ainsi que l'inhibition de l'infectivité par le sel résulte beaucoup plus d'une sensibilité de la plante hôte et particulièrement de la restriction de son alimentation calcique que d'une action directe de cette contrainte sur le microsymbiote [10,32,41]. Cependant, d'autres études montrent que l'action du sel s'exerce à des stades postérieurs à celui de la reconnaissance plante hôte-bactérie.…”
Section: Introductionunclassified
“…La ramification du cordon d'infection ainsi que sa migration à travers le cortex nodulaire sont aussi affectées par le sel [3,12,42]. Indépendamment de son mode d'action, l'effet du sel aux stades précoces de la nodulation se traduit par une réduction du nombre de nodules observée chez de nombreuses légumineuses, Glycine max [5,13] ; Cicer arietinum [9,16,23,35] ; Vigna radiata [10].…”
Section: Introductionunclassified
“…Most studies reported that nodule activity was less affected by salinity than nodulation [1,11,29] which may be related to salinity inhibition of root-hair expansion and curling [31]. However, Serraj, Roy and Drevon [26] showed that exposure of intact soybean plants to 0.1 M NaCl resulted in a rapid decrease in nitrogenase activity and nodule respiration, which was attributed to limitation of intranodular oxygen diffusion by salinity [24,27,28].…”
Section: Introductionmentioning
confidence: 99%